Comparative analysis of nanotechnology awareness in consumers and experts in South Korea - Kim YR (Dove Medical Press, 2014)
Yu-Ri Kim,1 Eun Jeong Lee,1 Sung Ha Park,2 Hyo Jin Kwon,3 Seong Soo A An,4 Sang Wook Son,5 Young Rok Seo,6 Jae-Eun Pie,7 Myoung Yoon,8 Ja Hei Kim,8 Meyoung-Kon Kim1 1Department of Biochemistry and Molecular Biology, Korea University Medical School and College, Seoul, South Korea; 2Department of Biochemistry, University of Bath, Bath, UK; 3Department of Medical Education, Korea University Medical School and College, Seoul, South Korea; 4Department of Bionanotechnology, Gachon University, Seongnam, Gyeonggi, South Korea; 5Department of Dermatology, Korea University Medical School and College, Seoul, South Korea; 6Department of Life Science, Institute of Environmental Medicine for Green Chemistry, Dongguk University, Seoul, South Korea; 7Department of Food and Nutrition, College of Science and Engineering, Anyang University, Anyang, Gyeonggi, South Korea; 8Consumers Korea, Seoul, South Korea Purpose: This study examined the need for public communication about nanotechnologies and nanoparticles by providing a comparative analysis of the differences in risk awareness of nanotechnologies and nanoparticles between consumers and experts. Methods: A total of 1,007 consumers and 150 experts participated in this study. A questionnaire was prepared examining their awareness of nanotechnologies and nanomaterials and their view of the necessity for information and education about the latest nanotechnologies and nanomaterials. Results: Our results indicated that the expert group recognized that they knew more than consumers about nanotechnology and that there was a need for relevant education in nanotechnology and nanomaterials among consumers. We found that the consumer group had a more positive attitude toward nanotechnology, even though they did not know much about it. Moreover, the consumer group was inconclusive about the type of information on nanotechnology deemed necessary for the public, as well as the suitable party to be responsible for education and for delivering the information. Conclusion: An education and promotion program targeting consumers should be established to overcome the differences between consumers and experts in their awareness of nanotechnology. Specifically, the establishment of concepts for nanomaterials or nanoproducts is required immediately. With clear standards on nanomaterials, consumers can make informed decisions in selecting nanoproducts in the market. Keywords: comparative analysis, survey, consumers, experts, nanomaterials